2016
DOI: 10.1186/s12909-016-0576-6
|View full text |Cite
|
Sign up to set email alerts
|

Role Models and Teachers: medical students perception of teaching-learning methods in clinical settings, a qualitative study from Sri Lanka

Abstract: BackgroundMedical education research in general, and those focusing on clinical settings in particular, have been a low priority in South Asia. This explorative study from 3 medical schools in Sri Lanka, a South Asian country, describes undergraduate medical students’ experiences during their final year clinical training with the aim of understanding the teaching-learning experiences.MethodsUsing qualitative methods we conducted an exploratory study. Twenty eight graduates from 3 medical schools participated i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 23 publications
1
20
0
2
Order By: Relevance
“…Regarding the theme of role modeling, it had positive effects on students in most of the cases. In a qualitative study about role modeling the results showed that clinical teachers’ awareness of their own obvious professional characteristics could help generate better teaching and learning experiences [ 23 ]. Another study showed that clinical attributes, teaching skills, and personal qualities of clinical teachers are the characteristics that medical students reported for a good role model [ 24 ].…”
Section: Main Textmentioning
confidence: 99%
“…Regarding the theme of role modeling, it had positive effects on students in most of the cases. In a qualitative study about role modeling the results showed that clinical teachers’ awareness of their own obvious professional characteristics could help generate better teaching and learning experiences [ 23 ]. Another study showed that clinical attributes, teaching skills, and personal qualities of clinical teachers are the characteristics that medical students reported for a good role model [ 24 ].…”
Section: Main Textmentioning
confidence: 99%
“…It was moving to hear students talk about their experiences in clinics and a little unnerving to be reminded that students minutely observe what their teachers and peers do. Teachers should be made aware of the need to behave appropriately to serve as role models for their students lest the latter inadvertently adopt practices that are neither ethical, nor professional (19).…”
Section: Discussionmentioning
confidence: 99%
“…Improvisation may be part of innovation and creativeness but it sometimes promotes the hidden curriculum (34). The concept of the hidden curriculum positions the learning environment in the medical school as a cultural entity and a moral community, with its own definitions of good and bad; a sort of cultural ecosystem involving human interaction with the environment where lecturers and students contribute to the transmission of the hidden curriculum (34)(35)(36)(37). Because few aspects of learning in the hidden curriculum are explicitly taught and assessed, there is the risk of negative influences creeping in and being passed on from one group to the next, as students are infused with the community's social expectations (38).…”
Section: Challenges At Workmentioning
confidence: 99%